MACROSCOPIC AND HISTOLOGICAL ANALYSIS OF ENDOSCOPICALLY RESECTED RECTAL LESIONS - Frugis, Marcos Onofre (2022)
Background: Colorectal cancer (CRC) is among the most common malignancies worldwide. Colonoscopy is the exam of choice for the prevention of CRC due to its great diagnostic and mainly therapeutic capacity in the face of adenomatous lesions. Objective: To analyze the prevalence and the macroscopic and histological characteristics 2 of polypoid rectal lesions resected with endoscopic techniques and to assess whether endoscopic therapy is safe and efficient in the treatment of lesions located in the rectum. Method: Retrospective observational study with analysis of medical records of all patients undergoing resection of rectal polyps. Results: 123 patients with rectal lesions were evaluated, 59 men and 64 women and the mean age was 56 years. All were submitted to endoscopic resection, with polypectomy in 70% and wide mucosectomy in 30%. Complete colonoscopy with removal of the entire rectal lesion occurred in 91%, and in 5% the preparation was inadequate, and precarious clinical conditions were impeditive factors, and in 4% surgical treatment was indicated because it was an infiltrative lesion with central ulceration. The histological evaluation showed adenomas in 3.25%, hyperplastic in 7.32% and hamartoma in 0.81%, low-grade dysplasia was identified in 34.96%, and high-grade dysplasia in 51.22%, adenocarcinoma in 1.63% and 0.81% being one of the cases classified as erosion. Conclusion: Polyps in the rectum are common, occurring in 37% of colonoscopies. Adenomas with dysplasia were the most common. Therapeutic colonoscopy proved to be a safe and efficient method for the complete treatment of rectal lesions